1987
DOI: 10.1128/iai.55.8.1801-1805.1987
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various diets on toxin production by two strains of Clostridium difficile in gnotobiotic mice

Abstract: When axenic mice fed a commercial diet were monoassociated with two toxigenic strains of Clostridium difficile, 100% of them died 3 days after inoculation and both enterotoxin and cytotoxin were produced in their intestinal tract. However, when axenic mice were fed various semisynthetic diets before C. difficile challenge, some of them survived and their fecal cytotoxin and enterotoxin productions were highly reduced, whereas the C. difficile population level did not decrease to a great extent. Thus, gnotobiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…Toxin A used in the test (produced by C. difficile) was crude. It was obtained from dialysis cultures of C. difficile as previously described (17) and stored at -20°C until use. Cholera toxin was purchased from Sigma Chemical Co., St. Louis, Mo.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Toxin A used in the test (produced by C. difficile) was crude. It was obtained from dialysis cultures of C. difficile as previously described (17) and stored at -20°C until use. Cholera toxin was purchased from Sigma Chemical Co., St. Louis, Mo.…”
Section: Methodsmentioning
confidence: 99%
“…Toxin A quantities were determined by using an enzymelinked immunosorbent assay (ELISA) procedure previously described (17). Only toxin A is revealed by this test.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic and biochemical evidences have shown that TcdC interferes with TcdR‐containing RNA polymerase and thus inhibits C. difficile toxin synthesis (Voth and Ballard, ; Matamouros et al ., ). Further details on toxin effects on infected host can be found in Burdon et al ., (), Mahe et al ., (), McFarland et al ., (), Ward and Young () and Akerlund et al ., ().…”
Section: A Brief Description Of Relevant Pathways In Pathogen (C Difmentioning
confidence: 97%